Corporate prosecutions: American law enforcement in global markets - Cornelia Woll (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2022)
Large companies are increasingly on trial. Over the last decade, many of the world's biggest firms have been embroiled in legal disputes over corruption charges, financial fraud, environmental damage, taxation issues or sanction violations, ending in convictions or settlements of record-breaking fines, well above the billion-dollar mark. For critics of globalization, this turn towards corporate accountability is a welcome sea-change showing that multinational companies are no longer above the law. For legal experts, the trend is noteworthy because of the extraterritorial dimensions of law enforcement, as companies are increasingly held accountable for activities independent of their nationality or the place of the activities. Indeed, the global trend required understanding the evolution of corporate criminal law enforcement in the United States in particular, where authorities have skillfully expanded its effective jurisdiction beyond its territory. This paper traces the evolution of corporate prosecutions in the United States. Analyzing federal prosecution data, it then shows that foreign firms are more likely to pay a fine, which is on average 6,6 times larger.
urn:nbn:de:hebis:30:3-651729
Keywords: 330; Wirtschaftskriminalität; Gesellschaftsrecht; Rechtsdurchsetzung; USA; Welt